Implementasi Konsep Mindfulness Dalam Kurikulum Sekolah Untuk Mengurangi Dismenore Primer Pada Siswi Putri - Roni Rowawi; Lina Herlina (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
Dysmenorrhea is a common problem experienced by adolescent girls and can cause problems in daily activities, especially learning activities at school. This disorder not only affects student attendance but also has an impact on a reduced quality of life. This study aims to determine the implementation of the mindfulness concept in the school curriculum as an effort to reduce primary dysmenorrhea in female students of SMAN 5 Karawang. This study employed a qualitative approach with the principal, school stakeholders, physical education, sports and health (PJOK) teachers, and female students of SMAN 5 Karawang as subjects. The results of the study describe a low understanding of the competency standards and basic competencies of PJOK related to mindfulness material. Limitations also exist in human resources and supporting facilities, so that the implementation of mindfulness education is not optimal. Nevertheless, the overall attitude of informants is very supportive of the integration of mindfulness material into PJOK learning. It is recommended that schools improve teacher capacity through cross-sector coordination with health institutions, so that PJOK teachers can gain a better understanding of mindfulness, and curriculum implementation can be more effective.